Enhancing diets: A Nutrition Behaviour Change Strategy for Tanna, Vanuatu - Nabuuma, Deborah; Ekesa, Beatrice (Bioversity International, 2025)
This Nutrition Behaviour Change Strategy (NBCS) was developed as a guide for nutrition interventions, activities, and communication within a nutrition-sensitive agriculture project in Vanuatu. The NBCS was participatorily developed particularly for Tanna, Tafea province, but is also applicable to other communities within the province and other provinces in the country. The aim of the NBCS is to improve diet quality among rural communities in Tanna, particularly women and children, by enhancing increased production and consumption of healthy sustainable diets from diverse locally available foods. The NBCS lays out the specific desired behaviours for different target groups, the key issues related to the behaviours, and approaches that can be used to address the key issues. The priority target groups are rural households with land access and those with limited land access, and youth. Also presented are the target influencing groups and examples of materials and key messages.